Piperlongumine as anticancer agent: The story so far about killing many birds with one stone - Farooqi, Ammad Ahmad; Attar, Rukset; Yaylim, Ilhan; Qureshi, Muhammad Zahid; Todorovska, Milica; Karatoprak, Gökçe Åžeker; Najafi, Saeideh; Sabitaliyevich, Uteuliyev Yerzhan; Zhenisovna, Tokmurziyeva Gulnara; de Sousa, Damiào Pergentino; Lin, Xiukun (Cellular and Molecular Biology, 2018)
Piperlongumine is a biologically and pharmacologically active constituent of the plant Piper longum. This compound is gradually gaining attention because of its ability to inhibit/prevent different cancers. Modern era of molecular oncology is incomplete without ground-breaking discoveries made in the field of cell signaling pathways. High-throughput technologies have considerably improved our understanding about wide ranging signal transduction cascades which play crucial role in cancer development and progression. It is exciting to note that piperlongumine has been shown to pleiotropically modulate different oncogenic signaling pathways. We partition this multi-component review into discrete sections and categorically summarize key findings related to excellent ability of piperlongumine to therapeutically target JAK-STAT, NF-kB and PI3K/AKT/mTOR pathways. We also set spotlight on regulation of TRAIL pathway and autophagy by piperlongumine in different cancers. On the basis of the current understanding of piperlongumine, molecular biologists and pharmacologists will develop the next generation of translational studies, which will prove to be helpful in improving the clinical outcome and getting a step closer to personalized medicine.